RELIGIOUS EXCLUSIVISM AND REFUGEE CRISIS IN A GLOBALIZED WORLD - Dushka Matevska; Zoran Matevski (UNIVERSITY "SS CYRIL AND METHODIUS UNIVERSITY"-SKOPJE FACULTY OF PHILOSOPHY, 2018)
The pseudo-democratic processes in Europe, the Balkans and R. Macedonia are a means of ruling the majority, wherein the leaders of those pro cesses succeed in manipulating the unthinking masses using Christian scripture. This research is trying to answer the question: If and when is a religious worldview a foundation through which the masses are mobilized and the fascistization of society, in which Christian and Islamic values become simple commodities in the neoliberal capitalism, is carried out? Does denying the right of others to be different from you means you are moving into the space of open and concealed violence) This problem arises when a so-called overlap between right-winged political forces and their ideologies is established. The problem is that original Christianity and Islam are falsified and used by the political right in the western Balkan states to define society as an organic national, ethnic and racial whole, which is primarily oriented towards national and patriarchal va lues. In the case of the Republic of Macedonia, the division of people between "us" and "them"; Macedonians and non-Macedonians; believers and atheists, breeds violence which is founded on a totalitarian understanding of faith. The idea that God is one, and the belief in Him is differently placed in different religions, can lead some individuals, religious and political organizations to the false notion that we are "us" because we are not "them" and the on ly way to remain "us" is to exterminate "them". Because of this, religious exclusivism leads to a violent ideology and religious extremism.
Keywords: religious exclusivism, religio us values, religious extremism, refugees